2011
DOI: 10.1007/s11814-010-0504-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of co-existing heavy metals and organophosphate pesticide on adsorption of atrazine to river sediments

Abstract: Adsorption characteristics of atrazine (AT) onto the surfacial sediments (natural surface coating samples) were investigated via thermal adsorption in the presence of pollutants malathion (Ma) and heavy metals (cadmium and copper). The results indicate that cadmium and Ma both have synergetic effect during the adsorption of AT; at the same time, copper caused antagonistic effect on the adsorption of AT. Ma could facilitate the adsorption of AT, no matter that Ma was added after the adsorption of AT or simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Currently, given that organophosphates and metals are common pollutants in the environment, more research is needed to study the combined toxic effect of organophosphates and metals. , Both CPF and Cd had nephrotoxicity, and the induction of oxidative stress is pivotal for their nephrotoxicity. , Generally speaking, additive responses, which means that the toxicity of combinations of chemicals equals to the sum of individual chemical response, would be expected . Although no statistical interaction was present between the CPF and Cd in kidney, the combination of CPF and Cd was still less toxic than the sum of the two chemicals alone.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, given that organophosphates and metals are common pollutants in the environment, more research is needed to study the combined toxic effect of organophosphates and metals. , Both CPF and Cd had nephrotoxicity, and the induction of oxidative stress is pivotal for their nephrotoxicity. , Generally speaking, additive responses, which means that the toxicity of combinations of chemicals equals to the sum of individual chemical response, would be expected . Although no statistical interaction was present between the CPF and Cd in kidney, the combination of CPF and Cd was still less toxic than the sum of the two chemicals alone.…”
Section: Discussionmentioning
confidence: 99%
“…The most accessible forms of metals for benthic organisms are those dissolved in the pore water of sediments [ 70 ]. A study [ 71 ] explored how Cd 2+ and Cu 2+ ions affect the sorption of atrazine, a common herbicide, by bottom sediments. The research revealed that Cd enhances the sorption of atrazine synergistically, while Cu has an antagonistic effect.…”
Section: Use Of the Invertebrates As Biosensors In Water Quality Moni...mentioning
confidence: 99%
“…It has been demonstrated that a combined pollution of pesticides with metals in soil could lead to deleterious effects on microbial communities due to toxic synergistic effects (Dewey et al 2012;Olaniran et al 2013). Moreover, the presence of metals in soil may affect the behavior of pesticides, increasing or decreasing their sorption, and therefore their bioavailability (Leistra and Matser 2004;Li et al 2011;Qian et al 2011;Pei et al 2014). In this sense, it has been reported that copper promotes the adsorption of carbendazim or iprodione (Leistra and Matser 2004) and causes antagonistic effects on atrazine sorption (Qian et al 2011).…”
Section: Introductionmentioning
confidence: 99%